(untitled) (Global Journal of Science Frontier Research, 2023)
Otolith morphology analysis is one of the main tools used for fish or stock identification. Moreover, otolith shape can also be used in the fish feeding studies (stomach content) for the identification of prey fish and their size according to the relationship between fish and otolith sizes. In the present study, the relationship between fish length and otolith morphological dimensions was investigated for Sargocentron spiniferum (Forsskål, 1775) (family: Holocentridae). The samples (185 fish and 370 sagittal otoliths) were collected from the coast of the Red Sea, Egypt. The statistical analysis was undertaken in two steps using generalized linear models for the relationship between body length and weight and otolith morphology descriptors (length, width, area, and perimeter) and shape indices (aspect ratio, compactness, form factor, rectangularity, roundness, ellipticity, squareness, sulcus, and ostium). From the relationships between total length (TL) of fish and fourteen morphology descriptors and shape indices, three are significantly correlated with TL (otolith length, cauda, and squareness) where the side effect were p